Impact of ICT on community development in ESCWA member countries - United Nations. Economic and Social Commission for Western Asia. (New York United Nations, 2009)
The challenges of measuring such a multifaceted concept as the information society render this task very complex. Although using measurements as a basis for evaluating and modifying strategies and policies is a sound approach, the relevance and accuracy of the selected tools remains questionable. In the past, measurement approaches were confined to simply aggregating a variety of data on selected ICT indicators, adjusting the weight of some factors, and applying statistical tools. These approaches, however, lacked theory and validation. While measuring the ever-changing ICT landscape might seem to be enough, the study emphasizes that societies are not exclusively driven by technology. Consequently, assessment efforts should go beyond measuring ICT diffusion and investigate the social context within which these developments are taking place. The study describes the efforts and progress made by the international community for measuring the information society. It draws particular attention to developing a unified model which is able to address the many aspects of the information society, including the impact of ICT on community development. Moreover, it investigates evaluation mechanisms that are able to assess the pivotal role telecenters play in developing communities in the ESCWA region, especially at the micro level. Despite the challenges and limitations, the study proposes a contextual framework and a set of indicators for measuring the impact of ICT on community development.--Publisher's description.
1. Measuring the information society -- 2. Case studies of community development projects -- 3. Measuring the impact.
Cover title.
Also available online
Keywords: Information technology -- Middle East; Community development -- Middle East